PENGENALAN PEMERINTAHAN DAN PENYUSUNAN PERATURAN DESA YANG BERKAITAN DENGAN PERLINDUNGAN ANAK DI DESA SAMUDA - asgar, Sukitman; Kartianti, sahrestia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2022)
This service activity carried out in Samuda Village aims to determine the understanding and skills of the village government related to the implementation of village government and the preparation of village regulations. the method used in the implementation of this service is the workshop and counseling which is carried out through the observation stage to find out the conditions and problems of Samuda Village and direct socialization to introduce the importance of the implementation of the service and the last is the extension stage or the implementation of Service, the participants consist of the Village Government, BPD, Leaders Customs and Community Leaders in Samuda Village, West Galela sub District. The results show that there is an increase in understanding and skills in terms of the village government already knowing its duties and obligations including the preparation of Village Regulations properly and effectively in the sense that the products produced will be based on stages and processes that are in accordance with the provisions of the legislation to be successful and efficient.